Study of the principles of regulation of innovative activities - Mekhovich, E. S.; Vorvul, A.; Dyakova, N.; Pererva, P. G. (My University, 2022)
The necessity of carrying out a strategic, comprehensive, effective state innovation policy, with the help of which Ukraine will be able to catch up with the industrially developed countries of the world and occupy the place it needs, has been established. The state creates organizational, economic and legal conditions for innovative activity.
Вивчення принципів регулювання інноваційної діяльності
Keywords: innovative activity; principles of regulation; state policy; sustainable development